Unacknowledged influence of existentialism in three selected English novels - Jalil, Nabeel Abdul Razaq (2013)
The research examines three selected English novels for selected elements of existentialism. The philosophy of existentialism was spreading widely in Europe in the middle of the twentieth century, especially after the Second World War. Its influence was not limited to the academic studies, but it affected literature and arts in general. It was spearheaded by two prominent figures, Jean-Paul Sartre and Albert Camus in France, whose literary works and activities made the philosophy relevant to the everyday life of people, particularly in their home country. Yet it seems that the philosophy had a negative reception in the English speaking world, especially England, among scholars and writers. There is not any well known English writer from that time, who is known publicly, who had acknowledged the influence of the philosophy in his/her works. Particularly those of the three selected novels. The research takes the counter point,presented by some scholars, who argue that after many decades of the retreat of existentialism behind modern and contemporary literary theories, (such as Marxism, psychoanalyses, feminism and post colonial theories), the influence of existentialism is still evident. The research selects three novels, (A Portrait of the Artist as a Young Man by James Joyce, Nineteen Eighty-Four by George Orwell, and Pincher Martin by William Golding), to examine them for selected concepts of existentialism, (freedom of choice and bad faith taken from Sartre's philosophy, the absurd and absurd rebellion taken from Camus's philosophy). The study aims to establish that the influence of existentialism can still be seen in some of the works of the selected English writers of that period, even though it was not acknowledged by critics at that time. And therefore, there are some elements of existentialism which can be found in literary works of some writers who are outside the league of the well known existentialist writers.